Senegal : Poverty Reduction Strategy Paper-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2007)
This Joint Staff Advisory Note reviews Senegal's Second Poverty Reduction Strategy Paper (PRSP-II), and provides advice on key priorities for strengthening the updated strategy and promoting its effective implementation. The PRSP-II, covering 2006-10, builds on lessons learned during the implementation of the 2003-05 Senegal Poverty Reduction Strategy (PRSP-I). The PRSP-II pushes the poverty reduction agenda forward so as to meet the objective of raising economic growth to about 7 percent per year necessary to halve poverty by 2015.